Determination of Insertion Loss of Acoustic Barriers under Specific Conditions. (2017) - Jagniatinskis, Aleksandras; Fiks, Boris; Mickaitis, Marius
Abstract: The World Health Organization the noise from road traffic composes as a main contribution in the total environment noise. In suburbia areas near the highways road traffic produce especial high noise levels. The acoustic barriers along the roads are designed to reduce this noise impact in protected against noise areas. The effectiveness of such barriers is expressed by "insertion loss" descriptor and determined from an in-situ measurement according to ISO 10847 standard that cover only typical in-situ situations. But there are some cases when the additional efforts are needed for adequate/realistic insertion loss determination. When, local connection road is constructed inside the barrier protected area and noise from this road mask the sound penetrating through the barrier from the highway. In such case insertion loss cannot be measured directly by standard procedure. In such specific conditions the application of provisions of the ISO 1996 series standards can be adopted to highway's noise extraction from total environmental noise measured inside protected area. The appropriate methodological solutions of discussed problems with the practical results of in-situ experimental measurements are presented.